Peran loyalitas pelanggan dalam memediasi kepuasan pelanggan terhadap niat berbelanja kembali - Immanuel Candra Irawan (Vikara: Student Academic Journal of Business and Management, 2025)
This study empirically examines the mediating role of customer loyalty in the relationship between customer satisfaction and repurchase intention within the context of modern retail stores in Nabire, Central Papua. Utilizing a quantitative methodology, data were collected via an online survey from 198 purposively sampled consumers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that customer satisfaction exerts a significant positive influence on both customer loyalty and repurchase intention. Furthermore, customer loyalty significantly affects repurchase intention and fully mediates the relationship between satisfaction and repurchase behavior. The study concludes that loyalty serves as a pivotal psychological mechanism converting transient satisfaction into enduring repurchase intentions. These results imply that retailers in emerging markets like Nabire should implement strategies that not only enhance customer satisfaction but also systematically cultivate deeper loyalty to secure long-term consumer retention.